Kepemimpinan Kepala Madrasah dalam Mengembangkan Budaya Mutu di MAN Model Jember - Prabowo, Sugeng Listyo (Jurnal Aplikasi Manajemen, 2012)
This study aimed at: 1) describing the characteristics of quality culture in the MAN ModelJember, 2) getting an overview of the leadership steps taken by the principal of the Madrasah in developinga quality culture of in the MAN Model Jember, 3) getting a description of efforts made by the principal toeliminate resistance in the quality culture development in the MAN Model Jember, and 4) obtaining anoverview of achievements as a result of a quality culture development in the MAN Model Jember. This studyis case study designed research using the informants'determination snowballing technique in which theprincipal of the Madrasah is the key informants. The data was taken by using the in-depth interviewtechnique, participant observation, and document retrieval. The data collected was then analyzed usingtheme analysis, subsequent to the triangulation and data reduction process. The result of the study indicatesthat the management and leadership of MAN Model Jember develop quality culture characteristicsbased on the following values: 1) discipline, 2) submission to Allah SWT and 3) the desire to constantlydevelop. The steps taken by the principal include: 1) the delegation of authority to the Deputy Principal, 2)improvement of the Madrasah management system, 3) making the values written statements, and 4) optimizingthe available opportunity. Resistance arising due to various changes include: 1) unpunctuality, 2)leaving the classroom while teaching-learning activity in progress, 3) often ending the lesson early, and 4)frequently absent. To overcome the resistance the principal take necessary actions including: 1) measurementof work performance using the scientific method, 2) negotiation and personal approach, 3) increasingthe teachers'job satisfaction, 4) continuous improvement, and 5) granting broad autonomy. The developmentof quality culture has impact on the: 1) madrasah's reputation in the community, 2) improvement of theacademic and non academic achievement. This study suggest to do benchmarking against the othermadrasahs having higher achievement, and to establish a teacher forum to formulate values and acculturationsystem of the values in Madrasah.